P595 Time of Therapeutic Drug Monitoring of infliximab during induction and its relationship with clinical remission in Inflammatory Bowel Disease. (30th January 2023) - Muñoz-Villafranca, C; Arreba, P; Gomez, M; Ispizua Madariaga, N; Buendia, L; Lopez, M L; Ugarte, A; de la Fuente, I; Prado, N; Irusta, L; Jimenez, M A; Santa Cruz, M; et al.
Abstract: Background: The usefulness of therapeutic drug monitoring(TDM) of infliximab during induction and its relationship with clinical outcome in patients with inflammatory bowel disease(IBD) is well established. However, the optimal time of monitoring in terms of clinical outcomes remains unclear. The aim is to evaluate the TDM at various times during induction and its association with clinical remission. Methods: An observational, retrospective and single-centre study of patients with active disease, Crohn's disease (CD) or ulcerative colitis(UC), was performed. Induction treatment with infliximab 0, 2, 6 weeks was conducted and if there was response, maintenance therapy was provided. Antibody levels were measured in serum samples at week 2 and week 14 by using an enzyme-linked immunosorbent assay, within the therapeutic range(3-8 µg/ml). Patients were followed at least for one year or until loss of response. The clinical response was assessed in week 14 and week 52 by Harvey-Bradshaw Index in CD and Mayo Partial Index in UC. Results: Out of 93 patients that were evaluated, 23 with UC(24.73%) and 70 with CD(75.27%, ), 65 (69.89%) and 58 patients(62.37%) achieved remission at week 14 and week 52 respectively. Infliximab levels at week 14 but not at week 2 were significantly higher in patients who achieved clinical remission in both week 14 (5.8 vs 2.1 µg/ml; p=0.0002) as in week 52 (6.4 vs 1.9 µg/ml; p=0.0001). The levels at week 14, but not at week 2 had predictive value of remission, in both week 14 [OR 1, 4 (CI 1.14-1.76) p=0.001] and week 52 [OR 1.4 (CI 1.15-1.87); p=0.001]. The patients with immunosuppressants at week 14 presented the highest rate of remission in week 52 (77.78 vs 52.63; p=0.014). The intensification of treatment was a negative factor to achieve remission both in week 14 and at week 52. Conclusion: The levels of infliximab in week 14 are higher and have predictive value of clinical remission both in early (week 14) and long-term (week 52). Levels of infliximab in week 2 did not provide significant predictive value of clinical response. The use of immunosuppressants could be a favourable factor of clinical outcome.